Translation Strategies for Slang Words in the Subtitles of Film “Inside Out 2” - Rahmah, Annisa Aulia; Wildan, Giazmara Galih; Fitriyah, Fitriyah (Universitas Nasional, 2024)
Translation is the process of conveying the meaning of a text accurately into a target language. Slang refers to informal language commonly used in casual conversations, making it unsuitable for formal situation. This study investigates the types of slang words and the translation strategies used in the subtitles of the movie Inside Out 2. Drawing on Allan and Burridge’s (2006) classification, the research identifies four types of slang—fresh and creative, flippant, imitative, and clipping—across 229 instances in the movie. Additionally, Baker’s (1992) translation strategies were analyzed to determine the most effective methods for rendering these slang expressions into the target language. The findings reveal that